THE ANALYSIS OF THE PROPORTION OF LANGUAGE SKILLS IN ENGLISH TEXTBOOK GRADE XI PUBLISHED BY KEMENDIKBUD 2014 - Wulandari, Yuni; Damayanti, Indah; Harahap, Alamsyah (Journal of English Education and Teaching, 2018)
This study analyzed the proportion of language skills in English textbook using descriptive quantitative method. This study aimed to find out the proportion of language skills in English textbook grade XI published by Kemendikbud 2014, and to find out the suitability of language skills in English textbook grade XI published by Kemendikbud 2014 and the goal of English subject's syllabus for Senior High School. The object of this research was English textbook for grade XI (Senior High School) published by Kemendikbud 2014 (1st and 2nd semester). The instrument used was evaluation checklist to collect the data about the proportion of language skills. The result showed that the textbook focuses more on writing skills (35%), grammar (32%), speaking (25%), reading (7%), and listening had the lowest proportion of (1%). The result of the evaluation showed that this textbook represent the writing skill that integrated with other skills. This textbook has the appropriate proportion on  two  skills (writing and speaking) however, it has inappropriate proportion on other two skills (listening and reading).